Manajemen Strategi Kepala Sekolah Dalam Meningkatkan Kompetensi Profesionalisme Guru - Tini Apriani Raga; Debora Fios; Djulia Lay Geda; Fendy Agusta Tualaka; Efri Tida Lumbu; Yanti Yunita Erni Sole (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
Teacher professionalism competency is a major determining factor in the quality of education, so it requires the role of the principal's leadership strategy to facilitate the development of these competencies in a sustainable manner. Professionalism is a key element that influences the quality of education, therefore strategic leadership from the principal is needed to support the development of competencies in a sustainable manner. This study aims to analyze and describe the principal's strategic management in improving teacher professionalism competency. The purpose of this study is to tell and explain how the principal manages strategies to develop teacher professionalism. This study uses the method used is a literature review with various sources of literature in the form of scientific, books, and relevant articles. The research subjects consisted of the principal, vice principal for curriculum, and teachers who were selected purposively. The results of the study indicate that the principal's management strategy in improving teacher professionalism competency is implemented through four main strategies, namely: systematic and measurable professional program development planning; implementation of periodic and needs-based academic supervision; empowerment of professional learning communities through the Subject Teacher Consultation (MGMP) forum and teacher working groups; and the provision of awards and motivation that encourage the continuous improvement of quality culture.